Cannabis Use Disrupts Eyeblink Conditioning: Evidence for Cannabinoid Modulation of Cerebellar-Dependent Learning - Skosnik, Patrick D. (2007)
While the cerebellum contains the highest density of cannabinoid receptor (CB1) in the brain, no studies have assessed the effect of exogenous cannabinoids on cerebellar-dependent learning in humans. The current study therefore examined the effect of chronic cannabis use on classical eyeblink conditioning (EBC), a cerebellar-mediated task which has been shown to be disrupted in CB1 knockout mice. Chronic cannabis users (24 hours abstinence prior to study; positive THC urine drug test) free of DSM-IV Axis I or Axis II disorders, were evaluated. A delay EBC task was utilized, in which a conditioned stimulus (CS; 400 ms tone) co-terminated with a corneal air puff unconditioned stimulus (US; 50 ms), thus eliciting a conditioned blink response (CR). The cannabis group exhibited markedly fewer, and more poorly timed CRs as compared to drug-nal̈ve controls. There were no differences between the groups in either the UR or an EEG measure of selective attention to the CS (N100 auditory ERP), indicating that the disruption observed in the cannabis group was specific to CR acquisition. These results suggest that cannabis use is associated with functional deficits in the cerebellar circuitry underlying EBC, a finding which corroborates recent work in CB1 knockout mice.